1996
DOI: 10.1128/aac.40.4.924
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of IS1272, an insertion sequence-like element from Staphylococcus haemolyticus

Abstract: We have previously shown (G. L. Archer, D. M. Niemeyer, J. A. Thanassi, and M. J. Pucci, Antimicrob. Agents Chemother. 38:447-454, 1994) that some methicillin-resistant staphylococcal isolates contain a partial deletion of the genes (mecR1 and mecI) that regulate the transcription of the methicillin resistance structural gene (mecA). When a fragment of DNA inserted at the point of the mecR1 deletion was used as a probe, hybridization with multiple bands was detected for Staphylococcus haemolyticus genomic DNA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 34 publications
2
41
0
Order By: Relevance
“…An insertion sequence in the sdrC A region was found to be similar to the C-terminal region of Enterococcus faecium transposase IS1216V (EMBL: L40841), sharing 46% identity. In addition, its organizational structure was similar to transposon IS1272 [34]. As shown in Figure 1, the sdrC in this mutant from an Eastern Canada cow was totally different from that of other cows in the same region.…”
Section: Discussionmentioning
confidence: 79%
“…An insertion sequence in the sdrC A region was found to be similar to the C-terminal region of Enterococcus faecium transposase IS1216V (EMBL: L40841), sharing 46% identity. In addition, its organizational structure was similar to transposon IS1272 [34]. As shown in Figure 1, the sdrC in this mutant from an Eastern Canada cow was totally different from that of other cows in the same region.…”
Section: Discussionmentioning
confidence: 79%
“…Our studies have shown that CoNS strains contain ccrAB genes that are 100% identical to S. aureus (Hanssen et al , 2004, 2005). Another line of evidence is that IS 1272 is present in Staphylococcus haemolyticus and S. epidermidis but is less frequently found in S. aureus (Archer et al , 1996). Staphylococcus aureus and S. epidermidis have identical IS 1272– Δ mecR1 junction sequences in SCC mec type I and IV (Wisplinghoff et al , 2003).…”
Section: Genes On the Movementioning
confidence: 99%
“…The origins of the SSC mec are unknown and so far, no bacterial isolates of any other genera have been reported to carry this element. The presence of IS 1272 , an insertion sequence prevalent in Staphylococcus haemolyticus , in the SCC mec types I and IV led to the proposal that SCC mec type I was transferred from this species to S. aureus in the past [16].…”
Section: Evolutionary Origin Of Mrsamentioning
confidence: 99%